Nano silica and meso silica extracted from rice husk waste utilized for enhancing leather properties - Ebtasam; Md. Nahid Bin Hasan; Rupok Kumar Nayak; Md. Ahsanul Haque Milon; Md. Farhad Ali (Polymer Testing, 2025)
The final stage of the leather manufacturing process, known as leather finishing, is what gives leather its final qualities and aesthetic appeal. Applying solvents and binders that can interact with crust leather's surface to change its chemical composition and enable the fixation of colors and dyes is the finishing process. To obtain great performance, the finishing must be extremely compatible. Therefore, this study focused on the extraction of the nanoparticles from rice husk waste for using in leather finishing which can be the sustainable materials that not only enhance the quality and performance of leather but also led to the waste minimization. The highly active, polar, porous, and huge interior area of biogenic silica nanoparticles and mesoparticles make them an excellent substitute for manufactured silica. Meso-silica and nano silica has been extracted from the rice husk by sol-gel method. A comprehensive array of assessments, encompassing FTIR, TGA, SEM, DLS, XRD, Zeta Potential, water vapor permeability, tensile strength, color rub fastness, color fastness to water, finish film adhesion test, adhesion strength of finish film, resistance to water spotting, heat resistance test, lastometer test, percentage of silica yield and percentage of elongation at break was conducted to thoroughly evaluate the performance of meso silica, nano silica and leather finished with both the nano particles as well as without nanoparticles. The performance of leather finished with nanoparticles also compared with each other and conventionally finished leather. The findings revealed satisfactory physical and analytical characteristics of the nano silica and meso silica finished leather.